ALGEBRA TEACHING TECHNOLOGIES BASED ON FINNISH METHODS - Kuljonov Nadir Jonadil ugli (Galaxy International Interdisciplinary Research Journal, 2022)
In the modern system of lifelong education, it is important to apply the best world practices to improve the quality and efficiency of education. This article highlights the importance of “Analyzing Mathematics Teaching in Finnish Secondary Schools”.